Management Of Ziswaf Uin Su And Polmed Islamic Law Perspective - Tambunan, Abd Aziz; Yamamah, Ansari; Harahap, Arifuddin Muda (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Zakat, Infaq, Sadaqah and Waqf (ZISWAF) is part of Islamic philanthropy which is currently starting to receive a lot of full attention, both from the government and other parties. Empowering various forms of philanthropy is part of efforts to help solve various problems in the community and at the same time improve the community's economy, especially after the Covid-19 outbreak. ZISWAF’s various potentials deserve to be empowered and maximized to support the economic revival that is being pursued by the government. One of the management institutions is UIN SU and POLMED. In order to increase efficiency and usefulness, zakat must be managed institutionally and professionally in accordance with Islamic law. Through an empirical normative study, this research seeks to reveal the implementation of empowerment and management of Islamic philanthropic potential which is in fact part of Islamic sharia, namely ZISWAF in educational institutions in the dimension of Islamic legal studies. The research results show that in its management, POLMED among universities that have carried out philanthropic operations has not fully coordinated with local related institutions such as BAZNAS. This should be a problem because potential forces can be gathered well but seem to stand alone without good coordination. Moreover, distribution is only limited to intra-campus communities such as students and workers on campus, so there are allegations that distribution relies on several subjective recommendations. In addition, the existing supervisors are not fully involved in efforts to increase the transparency and accountability of ZISWAF management on campus. This research recommends that ZISWAF management adjust its governance in accordance with sharia provisions.